2011
DOI: 10.1016/j.abb.2011.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 1α,25-dihydroxyvitamin D3 in plasma membrane targets in immature rat testis: Ionic channels and gamma-glutamyl transpeptidase activity

Abstract: 1α,25-Dihydroxyvitamin D(3) (1,25D(3)) is critical for the maintenance of normal reproduction since reduced fertility is observed in vitamin D-deficient male rats. The aim of this study was to investigate the effect of 1,25D(3) in 30-day-old rat testicular plasma membrane targets (calcium uptake and gamma-glutamyl transpeptidase (GGTP) activity), as well as to highlight the role of protein kinases in the mechanism of action of 1,25D(3). The results demonstrated that 1,25D(3) induced a fast increase in calcium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 53 publications
5
25
0
Order By: Relevance
“…Sertoli cells in either control or treated group were incubated in serum free medium with or without 1,25-D 3 (1 nM) or curcumin (1 nM) or PMA (100 nM) for 1, 3, 6 and 24 h. In some experiments inhibitors (CM, CH, H-89, KT, dibAMPc, ST, Ro) were added 30 min before the incubation time and maintained for the whole incubation period. In all cases, the inhibitors' concentrations used were those that have previously resulted in inhibition in similar assays (Menegaz et al 2009, Menegaz et al 2010, Menegaz et al 2011Zanatta et al 2011a, Zanatta et al 2013Rosso et al 2012).…”
Section: Gamma-glutamyl Transpeptidase Assaymentioning
confidence: 99%
See 4 more Smart Citations
“…Sertoli cells in either control or treated group were incubated in serum free medium with or without 1,25-D 3 (1 nM) or curcumin (1 nM) or PMA (100 nM) for 1, 3, 6 and 24 h. In some experiments inhibitors (CM, CH, H-89, KT, dibAMPc, ST, Ro) were added 30 min before the incubation time and maintained for the whole incubation period. In all cases, the inhibitors' concentrations used were those that have previously resulted in inhibition in similar assays (Menegaz et al 2009, Menegaz et al 2010, Menegaz et al 2011Zanatta et al 2011a, Zanatta et al 2013Rosso et al 2012).…”
Section: Gamma-glutamyl Transpeptidase Assaymentioning
confidence: 99%
“…Since our previous studies showed that 1 nM 1,25-D 3 has a positive effect on GGT activity in rat testis (Zanatta et al 2011a), the same concentration was chosen to carry out these experiments in isolated Sertoli cells. Sertoli cells in either control or treated group were incubated in serum free medium with or without 1,25-D 3 (1 nM) or curcumin (1 nM) or PMA (100 nM) for 1, 3, 6 and 24 h. In some experiments inhibitors (CM, CH, H-89, KT, dibAMPc, ST, Ro) were added 30 min before the incubation time and maintained for the whole incubation period.…”
Section: Gamma-glutamyl Transpeptidase Assaymentioning
confidence: 99%
See 3 more Smart Citations